2011
DOI: 10.1039/c1cs15086c
|View full text |Cite
|
Sign up to set email alerts
|

The MXCXXC class of metallochaperone proteins: model studies

Abstract: Transition metal ions can be both beneficial and harmful to biological systems if not carefully regulated. A family of proteins that include a conserved sequence in their binding site of MXCXXC is responsible for delivery and homeostasis of different metals. Model studies present an effective tool for studying the parameters governing metal affinity, selectivity and other mechanistic aspects. Small-molecule, peptide-based, and advanced models will be presented, as well as functional models of potential industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 76 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…7 Here, we found that overexpression of ATX1 resulted in hypersensitivity to severe Cu deficiency. By contrast, overexpression of mutated ATX1 did not show the hypersensitivity.…”
mentioning
confidence: 86%
“…7 Here, we found that overexpression of ATX1 resulted in hypersensitivity to severe Cu deficiency. By contrast, overexpression of mutated ATX1 did not show the hypersensitivity.…”
mentioning
confidence: 86%
“…As a Cu chaperone, ATX1 cannot directly transport Cu across membranes, but it may deliver Cu to the target proteins for Cu trafficking. Yeast ATX1 and AtATX1 in Arabidopsis have been reported to chelate Cu in the binding site containing the MXCXXC conserved sequence (Pufahl et al, 1997;Shoshan and Tshuva, 2011;, which is important for Cudependent protein-protein interaction (Pufahl et al, 1997;Andrés-Colás et al, 2006;Puig et al, 2007;Shoshan and Tshuva, 2011;. The alignment of protein sequences revealed that OsATX1 contains an MXCXXC Cu + -binding motif (Supplemental Fig.…”
Section: Osatx1 Affects Cu Transport and Distribution Probably By Intmentioning
confidence: 99%
“…Yeast ATX1 was reported to chelate Cu with excellent affinity (Pufahl et al, 1997;Shoshan and Tshuva, 2011). Additionally, the MXCXXC motif of yeast ATX1 acts as a high-affinity Cu-binding site and is important for Cu-dependent protein-protein interaction (Pufahl et al, 1997;Shoshan and Tshuva, 2011).…”
mentioning
confidence: 99%
“…Additionally, the MXCXXC motif of yeast ATX1 acts as a high-affinity Cu-binding site and is important for Cu-dependent protein-protein interaction (Pufahl et al, 1997;Shoshan and Tshuva, 2011). The alignment of protein sequences revealed that ATX1 in Arabidopsis contains only one MXCXXC motif and the only known metal-binding motif (Supplemental Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation